A PROSPECTIVE STUDY ON QUALITY OF LIFE IN PATIENTS WITH ARTHRITIS - Devi G, Poojitha; S, Sathesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Patient counseling can scientifically improve the physical and mental symptoms of certain diseases that could be a relief to the patient. Non-pharmacological approaches could be an alternative to the drug therapy. Health issues affecting the quality of life (QoL) are to be studied to understand the patient’s physical, mental, emotional, and social functioning. Methods: The present study involves prospective analysis of QoL in men and women with arthritis. The methodology involves the collection and documentation of general information of the patient including personal history, family background, clinical findings, investigations, and medical illness associated with arthritis. Further, the QoL is documented using a specific questionnaire designed to assess the impact of arthritis and their complications. Results: It can be seen that there is no significant changes in the physical and mental component score (MCS) in between the type of arthritis, but there is an extremely significant (p<0.05) values were obtained when compared between pre- and post-counseling phases of physical and MCS. Conclusion: Patients counseling plays a major role in the management of signs and symptoms among patients with arthritis. The non-pharmacological method is also be used for the management of arthritis. Keywords: Quality of life, Arthritis, Patient counseling, Questionnaire, Physical component score, Mental component score.